THE ROLE OF FAITH/WORLDVIEW STYLES IN MUSIC PREFERENCE - Barış ERDAL (Fırat University, 2019)
In this study, the relation between music preference (within the frame of 10 music genres) and faith or worldview styles along with religious attitude was investigated. 187 university students were first asked to indicate the level of particular feelings (such as comfort, extraordinary, union with the universe and so on) on a Likert scale (not at all, little, moderate, much, very much) during or after listening to a variety of played music (such as Rap, Jazz, Tasavvuf-Muslim-Mystical Music etc.) in their presence. In this way, their music preferences were determined. Before they listen to the music, the participants first filled in the scales of faith schemas (absolute faith, open faith, transformation in faith, and tension in faith) religious attitude and value dimensions. The scales of certain music-lovers (such as the scales of Jazz-lover, Rap-lover so on) were obtained through the reliability analysis of the feelings rated on each of the music peace presented. The relationship of music lovers with the above-mentioned variables checked through correlation. The results show that some meaningful relationships are found between music preference and faith/ worldview styles.